PENGARUH SANKSI PERPAJAKAN, KUALITAS PELAYANAN, DAN MORAL WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN MOJOKERTO - Chadinamin Fadhilatil Maula; M. Cholid Mawardi; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study was to determine the effect of Tax Sanctions, Service Quality and Moral of Taxpayers on UMKM Taxpayer Compliance in Mojokerto Regency. This type of research is quantitative research. The population used in this study were UMKM users who were registered at the Department of Cooperatives and Micro Enterprises in Mojokerto Regency. The sampling technique used in this study is the Slovin formula and obtained a total sample of 100 respondents. The data collection method in this study used a questionnaire because the data collection techniques were carried out by giving a number of questions and written statements to respondents. Research data and hypotheses in this study were analyzed using SPSS 16.0. The results of this study indicate that the variables of tax sanctions, service quality and morality of taxpayers have an effect on tax compliance for UMKM.Keywords: Tax Sanctions, Service Quality, Taxpayer Morals, Taxpayer Compliance